The dynamics of linking permit markets - Katinka Holtsmark; Kristoffer Midttømme (University of Oslo, Department of Economics, 2015)
We present a novel benefit of linking emission permit markets. We consider a dynamic setting, and let the countries issue permits non-cooperatively. With exogenous technology levels, there are only gains from permit trade if countries are different. With endogenous technology, however, we show that there are gains from trade even if countries are identical. In this case, linking the permit markets of different countries will turn permit issuance into intertemporal strategic complements: If one country issues fewer permits today, other countries will respond by issuing fewer permits in the future. This happens because issuing fewer permits today increases current investments in green energy capacity in all permit market countries, and countries with a higher green energy capacity will respond by issuing fewer permits in the future. Hence, each country faces incentives to withhold emission permits. Even though countries cannot commit to reducing their own emission, or punish other countries that do not, the outcome is reduced emissions, higher investments, and increased welfare, compared to a benchmark with only domestic permit trade. The more frequently participating countries reset their caps, the higher the gain from linking permit markers.
Keywords: F53; Q54; H87; 330; international agreements; permit markets; dynamic games; green technology investments